Crude Bromelain Enzyme Activities Based on Maturity Level of Pineapple - Detris Poba; Ijirana Ijirana; Jamaludin Sakung (Jurnal Akademika Kimia, 2019)
Utilization of pineapple is always focused on consumption for fresh fruit and animal feed. many people do not know the other benefits of pineapple. The presence of protease enzymes in it, increasing its utilization. The enzyme is bromelin, which can be obtained by isolating it from pineapple. For this reason, the aim of this study is to isolate the crude bromelain enzyme based on the maturity level of pineapple and then test its proteolytic activity. Pineapple was blended, then the filtrate was deposited, then centrifuged to obtain crude bromelain which is dried by the drying method and tested for its activity using milk substrate. The results showed that old pineapple is the best level of maturity and the sun is the best drying method with proteolytic activity of 0.053 and 0.056 MCU/mg respectively. Its optimum activity is pH 5.8 and 55 oC.